Interaction between FliE and FlgB, a Proximal Rod Component of the Flagellar Basal Body of Salmonella - Minamino, Tohru (American Society for Microbiology, 2000)
FliE is a flagellar basal body protein of Salmonella whose detailed location and function have not been established. A mutant allele of fliE, which caused extremely poor flagellation and swarming, generated extragenic suppressors, all of which mapped to flgB, one of four genes encoding the basal body rod; the fliE flgB pseudorevertants were better flagellated and swarmed better than the fliE parent, especially when the temperature was reduced from 37 to 30°C. Motility of the pseudorevertants in liquid culture was markedly better than motility on swarm plates; we interpret this to mean that reduced flagellation is less deleterious at low viscous loads. Overproduction of the mutant FliE protein improved the motility of the parental fliE mutant and its pseudorevertants, though not to wild-type levels. Overproduction of suppressor FlgB (but not wild-type FlgB) in the fliE mutant also resulted in improved motility. The second-site FlgB mutation by itself had no phenotype; cells swarmed as well as wild-type cells. When overproduced, wild-type FliE was dominant over FliE-V99G, but the reverse was not true; that is, overproduced FliE-V99G was not negatively dominant over wild-type FliE. We conclude that the mutant protein has reduced probability of assembly but, if assembled, functions relatively well. Export of the flagellar protein FlgD, which is known to be FliE dependent, was severely impaired by the FliE-V99G mutation but was significantly improved in the suppressor strains. The FliE mutation, V99G, was close to the C terminus of the 104-amino-acid sequence; the suppressing mutations in FlgB were all either G119E or G129D, close to the C terminus of its 138-amino-acid sequence. Affinity blotting experiments between FliE as probe and various basal body proteins as targets and vice versa revealed strong interactions between FliE and FlgB; much weaker interactions between FliE and other rod proteins were observed and probably derive from the known similarities among these proteins. We suggest that FliE subunits constitute a junction zone between the MS ring and the rod and also that the proximal rod structure consists of FlgB subunits.